2005
DOI: 10.1063/1.2011405
|View full text |Cite
|
Sign up to set email alerts
|

Stable confinement of toroidal electron plasma in an internal conductor device Prototype-Ring Trap

Abstract: A pure electron plasma has been produced in an internal conductor device Prototype-Ring Trap (Proto-RT). The temporal evolution of the electron plasma was investigated by the measurement of electrostatic fluctuations. Stable confinement was realized when the potential profile adjusted to match the magnetic surfaces. The confinement time varies as a function of the magnetic field strength and the neutral gas pressure, and is comparable to the diffusion time of electrons determined by the classical collisions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…This method is directly applicable to the pure electron plasma experiments in Proto-RT, 8,15 which also have insulated rods in the plasma. In the pure electron plasma experiments in the Compact Helical System ͑CHS͒ stellarator, 13,16,17 electrons are injected from the outside, but diagnostic rods that are usually used inside the plasma 18 provide a mechanism for ion loss and therefore the ion rate balance is also analogous to that in CNT.…”
mentioning
confidence: 99%
“…This method is directly applicable to the pure electron plasma experiments in Proto-RT, 8,15 which also have insulated rods in the plasma. In the pure electron plasma experiments in the Compact Helical System ͑CHS͒ stellarator, 13,16,17 electrons are injected from the outside, but diagnostic rods that are usually used inside the plasma 18 provide a mechanism for ion loss and therefore the ion rate balance is also analogous to that in CNT.…”
mentioning
confidence: 99%
“…1͒. In investigating the internal potential structures of electron plasma in Proto-RT, 20,21 we found that the confinement properties were drastically improved when the shapes of potential contours were adjusted to those of the magnetic surfaces by negatively biasing the case of the dipole field coil. We have started studies on toroidal non-neutral plasma in a dipole magnetic field.…”
Section: Introductionmentioning
confidence: 92%
“…17 Proto-RT [19][20][21] was a prototype magnetospheric device with a dipole field coil that was mechanically supported in the chamber. 1͒.…”
Section: Introductionmentioning
confidence: 99%
“…In those experiments, the confinement time is typically measured through the decay rate of image charge on a capacitive probe placed outside the plasma. [9][10][11]21 The emitter filament is mounted near the end of a hollow 0.5 in. diameter ceramic rod.…”
Section: A the Cnt Devicementioning
confidence: 99%